Autoficção: a ocupação do eu no outro em Histórias de médico em formação de Moacyr Scliar - Montanari, Camila Bozza (2021)
This paper presents a study that focuses on the first work of the writer Moacyr Scliar. Produced from the experiences of the writer while he was a medical student, Histórias de médico em formação (1962) is a composition of eleven short stories chosen from those published in the college newspaper O Bisturi. The texts deal with the precariousness of public health in Brazil, poverty and death in similar scenarios, where the author's image is reflected in the characters' faces. These perceptions direct the inve stigation to the conceptions that guide the author in his death, function, position in the writing process and in the relations with another self, thus we base the analysis on the approaches of Barthes, Michel Foucault, Philippe Willemart and Bakhtin. Nevertheless, the research aims to ground the occupation of the self in the other from the theory of autofiction in the face of Moacyr Scliar's firstborn work. For this, we base the study on Vincent Colonna's conceptualization, arising from a theoretical path between the writing of the self and the fields of autobiography and autofiction. However, we justify the autoficiionalized author of Histórias de médico em formação based on other expressive texts of the writer's career: Uma autobiografia literária - O texto, ou: a vida (2017); Território da Emoção - Crônicas de medicina e saúde (2013); A paixão transformada - História da medicina na literatura (2011); e Cenas médicas - Pequena introdução à história da medicina (1987). The research conducted deals with a reunion to the young doctor and writer who, in an act of self-censorship, assigns his first published book to post -editorial discontinuity.